2010
DOI: 10.1016/j.dnarep.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between human mismatch repair recognition proteins and checkpoint sensor Rad9-Rad1-Hus1

Abstract: In eukaryotic cells, the cell cycle checkpoint proteins Rad9, Rad1, and Hus1 form the 9-1-1 complex which is structurally similar to the proliferating cell nuclear antigen (PCNA) sliding clamp. hMSH2/hMSH6 (hMutSα) and hMSH2/hMSH3 (hMutSβ) are the mismatch recognition factors of the mismatch repair pathway. hMutSα has been shown to physically and functionally interact with PCNA. Moreover, DNA methylating agent N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) treatment induces the G2/M cell cycle arrest that is depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 87 publications
0
20
0
1
Order By: Relevance
“…41 Furthermore, human RAD9A and MSH6 colocalize in nuclear foci following DNA methylating agent treatment, and RAD9A focus formation is dependent upon the presence of MSH6. 41 Li and coworkers also demonstrated that RAD9A is important for nucleotide excision repair by maintaining, among others, the protein level of the excision factor DDB2 in human cells, 43 and RAD9A-deficient mouse embryonic stem cells are slow to repair UV-induced DNA damage. 44 These repair-related functions of 9-1-1 are likely to be relevant to meiotic chromosome biology, as many of the DNA repair factors mentioned here have known or predicted roles in meiotic cells.…”
Section: The 9-1-1 Complex Functions In Atr Activation and Dna Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Furthermore, human RAD9A and MSH6 colocalize in nuclear foci following DNA methylating agent treatment, and RAD9A focus formation is dependent upon the presence of MSH6. 41 Li and coworkers also demonstrated that RAD9A is important for nucleotide excision repair by maintaining, among others, the protein level of the excision factor DDB2 in human cells, 43 and RAD9A-deficient mouse embryonic stem cells are slow to repair UV-induced DNA damage. 44 These repair-related functions of 9-1-1 are likely to be relevant to meiotic chromosome biology, as many of the DNA repair factors mentioned here have known or predicted roles in meiotic cells.…”
Section: The 9-1-1 Complex Functions In Atr Activation and Dna Repairmentioning
confidence: 99%
“…40 Multiple interactions have also been reported between 9-1-1 subunits and the DNA mismatch repair factors MutS homolog 2 (MSH2), MSH3, MSH6, and MutL homolog 1 (MLH1), 41,42 and mismatch recognition by the MSH proteins is stimulated by the presence of 9-1-1. 41 Furthermore, human RAD9A and MSH6 colocalize in nuclear foci following DNA methylating agent treatment, and RAD9A focus formation is dependent upon the presence of MSH6.…”
Section: The 9-1-1 Complex Functions In Atr Activation and Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the 9-1-1 complex may provide a platform for the assembly and function of the BER machinery (Balakrishnan et al, 2009;Lu et al, 2006). The 9-1-1 complex enhances mismatch repair via direct interaction with mismatch recognition proteins (MSH2/MSH3, MSH2/MSH6, and MLH1/PMS2) (Bai et al, 2010;He et al, 2008). Hus1 interacts with MSH2/MSH3 and MSH2/MSH6, but not with MLH1/PMS2 (Bai et al, 2010;He et al, 2008).…”
mentioning
confidence: 99%
“…The 9-1-1 complex enhances mismatch repair via direct interaction with mismatch recognition proteins (MSH2/MSH3, MSH2/MSH6, and MLH1/PMS2) (Bai et al, 2010;He et al, 2008). Hus1 interacts with MSH2/MSH3 and MSH2/MSH6, but not with MLH1/PMS2 (Bai et al, 2010;He et al, 2008). In the NER pathway, interactions between Saccharomyces cerevisiae Rad14 (hXPA homolog) and the checkpoint proteins ScDdc1 (hRad9 homolog) and ScMec3 (hHus1 homolog) have been demonstrated (Giannattasio et al, 2004).…”
mentioning
confidence: 99%